THE BUILDING ALGORITHM OF THE TABLE OF THE TRANSPOSITIONS BY THE CONSEQUENT INCREMENTATIONS METHOD - E. P. Pegova (Научный вестник МГТУ ГА)
Algorithm of the building of the table of the transpositions is оffered without repetitions from N element in the manner of numeric row.